KARAKTERISASI SENYAWA CICERFURAN DARI FRAKSI ETIL ASETAT EKSTRAK AKAR KAYU LABAN (Vitex pubescens Vahl) (Characterization of Cicerfuran Compounds From The Ethyl Acetate Fraction of Laban Root Wood Extracts (Vitex pubescens Vahl) - Evy Wardenaar Afghani Jayuska,Hikma Yanti (Universitas Tanjungpura, 2011)
One of the many traditional medicinial plant species found in West Kalimantan is Laban wood (Vitex pubescens Vahl) which extracts are used to treat diseases. Therefore it is expected that exist in the plant of bioactive compounds. This study aims to determine the bioactive compounds in root extracts of Laban from the ethyl acetate fraction to characterize the single compounds. The methods used was the isolation by chromatography column and identification by Liquid Chromatography Mass Spectroscopy (LCMS), Ultra Violet (UV), Infra Red (IR), Nuclear Magneitc Resonance (NMR) and Heteronuclear Multiple Bond Correlation (HMBC). The results obtained from spectrum data Mass Spectroscopy (MS), UV, IR, HMBC and NMR indicated presence of cicerfuran which is a stilbene derivative compound. Keywords : Cicerfuran, ethyl acetate, root extracts, Vitex pubescens Vahl